Planning Processes And Policy Implementation On The Information And Technology Resources Management - Ardianto, Yuli; Subhan, M. Nuruddin; Riskarini, Dian (The journal of contemporary issues in business and government, 2021)
Informɑtion today is a valuable “commodity” which tradeable thus it has high market price because information can contribute significantly in the process of very important decision making especially for organization. The objective of this article is to analyze several variables that significantly affect the planning processes and policy implementation in information and technology resources management. To achieve its objective, this study employed content analysis and eventually formulates a model to be further emphasized in the theme of information technology management. This study found seven important points of view in order to create an effective as well as efficient activities in the organization by utilizing information, technology, infrastructure and comprehensive library and ends up with proper and well-made decisions by the top management.